Effectivity Analysys Of Tampar Mendong Craftment Capacity Development Through Applied Technology Program At Blayu Sub-District, Wajak District, Malang - Rudianto Rudianto (Journal of Innovation and Applied Technology, 2015)
ABSTRACTTo assess whether aidequipment program for science and technology to mendong craftsman living in village of Blayu, in Blayu sub-district gives a positive impact for the recipient, so it is needed analysis to know how far such aidequipment program effectively to the people.For the purpose of this research is to know the effectiveness of aid equipment including its training is to encourage the growth of mendong production into quality need for local, regional and international market. The method to assess the effectiveness of development of mendong craftsmen is used descriptive analysis. Such analysis using the method of evaluation of the effectiveness of programs by using the table associated with the importance and effectiveness of the recipient. To assess such effectiveness is used method called Importance Performace Analysis (IPA).The results of this research showed that aid equipment is recognized extremely small, although it could increase production and reduce the hours of operation. This research resulted in the finding that the aid of mendong equipment can cause social jealousy.This is because the aid given only to a small group, while the other groups is not given aid yet.Keywords:aid equipment, effectivity, important performance analysis